Pre-combustion thermal properties of combustible extruded polystyrene obtained by high temperature heating - Kudryashov, Вадим Александрович; Ivlev, Юрий Петрович; Drobysh, Антон Сергеевич; Botyan, Сергей Сергеевич (Journal of Civil Protection, 2024)
Purpose. Based on experimental data and theoretical research, to assess the pre-combustion thermal properties of combustible extruded polystyrene insulation obtained by high-temperature heating and their influence on the fire resistance and fire hazard class of structures with profiled sheet roofing. Methods. Detailed examination of the behavior of combustible extruded polystyrene under elevated temperature conditions was conducted through testing of model samples using equipment for assessing flammability and determining flash point in an open crucible TVO-LAB-01 with an expanded base of measuring instruments. Findings. Model test results indicate that identical thermal damage is characteristic for samples from different manufacturers, acquired after surface temperature increases above 100 °C, with the formation of accumulations (clusters) of quasi-molten (damaged) material on the heated surface at temperatures around 120…140° C. As the temperature approaches to 160 °C, the damage becomes more pronounced, corresponding to melting. If the thermal power is insufficient to form a melt throughout the material volume, its shrinkage occurs until the temperature decreases along the axis of the heat flow to the melt temperature (120…140 °C).To assess thermal damage in large-scale tests, it is advisable to compare the damage to extruded polystyrene with Table 2 of this article, considering temperature measurement data. The fact of burning of extruded polystyrene can only be confirmed by the presence of foamed residue indicating boiling of the melt.To model the thermal damage of extruded polystyrene in the form of thermal shrinkage it is advisable to use a critical temperature which does not exceed 100 °C. Application field of research. The research results can be applied in the design and construction of structures with profiled sheet roofing using a combined approach to determine the required amount of combustible and non-combustible insulation, combustible roofing material, and vapor barrier.